Advantages Of Stock Exchange Lıstıng - Kadi, Xhensila (European Scientific Journal, ESJ, 2016)
The Stock Exchange is a regulated market of securities where contracts for the sale and purchase of the financial instruments are stipulated. The financial instruments such as stocks, bonds, derivatives with a definite price are traded and exchanged in the Stock Exchange. In this case the price is determined by the balance of supply and demand. If we would describe the Stock Exchange with an image, we would think a square in which some companies with public offer or companies with public participation operate. In particular, in it we may found industrial companies, financial companies, banks, services companies, etc. If we refer to history, the first and real trade of securities occurred around the year 1500 in Bruges. Nevertheless, Antwerp has been considered the first Stock Exchange, as the one of Bruges cannot be defined a genuine Stock Exchange. In Albania, till the end of 2014 we have had the Tirana Stock Exchange (TSE). The Tirana Stock Exchange was founded in 2002 in the form of a joint stock company, and has operated in accordance with the provisions of the Law No. 9901 dated 14.04.2008 “On the Entrepreneurs and trading companies” and the Law no. 9879, date 21.02.2008 “On Securities”. Initially, the listing of securities on the stock exchanges, for many entrepreneurs, meant an advertisement for the company, while now it is a widespread phenomenon in the world. If we refer to our country, we believe that the listing in the stock exchange has an important role towards the awareness of our companies regarding finding different manners from the traditional ones about their liquidity. Through this paper, it is aimed to answer to a fundamental question as the one related to the reasons why companies should be listed on the stock exchange. Each of the actions related to trading on the stock exchange is one of the steps in the process of investment, therefore we can say that this kind of financial transactions is not just about buying or selling a particular security.